2014
DOI: 10.1016/j.drugalcdep.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in drug use among polysubstance users

Abstract: Background Available evidence indicates women with substance use disorders may experience more rapid progression through usage milestones (telescoping). The few investigations of sex differences in treatment-seeking populations often focus on single substances and typically do not account for significant polysubstance abuse. The current study examined sex differences in a heterogeneous sample of treatment seeking polysubstance users. We examined patterns of drug use, age at drug use milestones (e.g., initial u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…Regardless of the explanations for these shifts, given evidence that cannabis use in women is associated with a faster progression to cannabis use disorder (Lewis et al, 2014) as well as greater risk for comorbid anxiety and depression during adolescence (Kloos et al, 2009), the findings raise concerns about the potential for increased cannabis-related harms among young women. Further, given that recent reviews have suggested that greater female vulnerability to cannabis use disorder may be linked to important biological differences such as neuronal maturation over adolescence, sex-specific responses to cannabinoid compounds, and hormone and cannabinoid receptor interactions (Kuhn, 2015;Rubino & Parolaro, 2015), increased cannabis use among adolescent females is of particular concern.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Regardless of the explanations for these shifts, given evidence that cannabis use in women is associated with a faster progression to cannabis use disorder (Lewis et al, 2014) as well as greater risk for comorbid anxiety and depression during adolescence (Kloos et al, 2009), the findings raise concerns about the potential for increased cannabis-related harms among young women. Further, given that recent reviews have suggested that greater female vulnerability to cannabis use disorder may be linked to important biological differences such as neuronal maturation over adolescence, sex-specific responses to cannabinoid compounds, and hormone and cannabinoid receptor interactions (Kuhn, 2015;Rubino & Parolaro, 2015), increased cannabis use among adolescent females is of particular concern.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, several studies have suggested that women who use cannabis are more vulnerable than men to the development of cannabis use disorder, particularly during adolescence (Kuhn, 2015) and that, following first use, they progress more quickly than men through the cannabis-related problems cycle (Lewis et al, 2014). Substantial changes over time in the sex distribution of cannabis use may require a rethink of effective prevention, public health, and intervention strategies to combat the harms and costs associated with cannabis use.…”
mentioning
confidence: 99%
“…Evidence also indicates that men and women differ in drug use initiation, relapse, and drug choice with women more likely to abuse prescription drugs than illicit substances (Fattore, Melis, Fadda, & Fratta, 2014). Women become immersed in serious drug use faster than do men (Bloom, Owen, Covington, & Raeder, 2003;Fattore et al, 2014;Lewis, Hoffman, & Nixon, 2014) and experience more rapid progression through drug use milestones (e.g., initial use, regular use, chronic use), particularly for pain medication and cannabis (Lewis et al, 2014).…”
Section: Female Criminality and Drug Usementioning
confidence: 96%
“…Other researchers have gone so far as to call for specific gender-responsive criminal justice policy (Bloom et al, 2004). Past research has also emphasized understanding potential differences in the needs and recovery processes of drug dependent male and female offenders to design optimal interventions (Anglin, Hser, & Booth, 1987;Lewis et al, 2014;Messina et al, 2006). Because women experience different, often gendered, pathways to drug abuse, crime, and desistance, reentry programming should ideally reflect these particular needs (e.g., trauma informed care, parenting issues, social support).…”
Section: Female Reentry and Rehabilitationmentioning
confidence: 98%
“…Furthermore, in the first study the tolerance-inducing dose was adjusted for sex differences in acute potency of THC, such that females received approximately 30% less THC than males did during the chronic treatment period, yet THC potency still decreased more in females than males. Epidemiological evidence indicates that women are more susceptible than men to rapid development of abuse and dependence on a variety of addictive substances, including marijuana (Khan et al, 2013; Lewis et al, 2014), and women are more likely than men to report physical withdrawal symptoms upon cessation of chronic cannabis use (Copersino et al, 2010). Given the significant role of drug tolerance in the development of substance abuse and dependence, females’ greater potential for developing cannabinoid tolerance may contribute to female cannabinoid users’ more rapid trajectory to abuse and dependence.…”
Section: Introductionmentioning
confidence: 99%